THE DETERMINANS OF EARNINGS RESPONSE COEFFICIENT: An Empirical Study for The Real Estate and Property Companies Listed on The Indonesia Stock Exchange - Widiatmoko, Jacobus; Indarti, MG. Kentris (Universitas Negeri Semarang, 2018)
Abstract This study aimed to examine the influence of the earnings persistence, growth, systematic risk, capital structure, and company’s size on the earnings response coefficient.The population of this research arethe real estate and property companies listed on the Indonesia Stock Exchange from 2011-2014.Samples were selected by using the purposive sampling method and obtained as much as 52, 52, 51 and 50 companies respectively. The ordinary least square regression was used in this research to analyze the data.The result shows that the earnings persistenceand capital structurehavepositive and significant effect on the earnings response coefficient, the company’s growth has negative and significant on earnings response coefficient, while systematic risk, and firm size have no effect on earnings response coefficient. Key words: earnings persistence, company’s growth, systematic risk, capital structure, company’s size and earnings response coefficient